Exploring EFL Students' Strategies in Writing Research Background at One of the Universities in Cirebon - Parwati, Iis; Sugesti, Ikariya (Allure Journal, 2023)
Learning strategies assist students in revealing their individual learning style, recognizing their identity as learners, and being conscious of their learning obstacles. The current study aimed to investigate the strategies in writing research background encountered by English Department students at one of Cirebon's institutions throughout the academic year 2021/2022. This study employed a qualitative technique with a case study design, with thirty students participating as respondents. The data was gathered via a questionnaire and an interview. There are two research instruments in this research, especially close-ended questionnaire and semi-structured interview.The instruments were also distributed in Bahasa Indonesia. According to the findings, students adopted strategies such as reviewing the references of journal articles. This causes students to use strategies to reduce these difficulties, including reading reference journals or articles. The score using this strategy is 95%. Furthermore, respondents indicated that they were requesting revisions from their supervisor.This is the experience of lecturers were better because they have done research many times. As a result, they were changing the sentence structure check.In addition, it creates sentences that are difficult to understand between sentences and paragraphs that are out of sync. There was a need for a revision of the review to produce a coherent reading and not confused the readers.It is suggested that the students choose the appropriate strategy, so that the strategy can be implemented properly.